On energy and self-regulation: A test of the Self-Regulatory Strength Model and Self-Determination Theory - Sharp, Elizabeth (University of Ottawa (Canada), 2008)
Self-regulation is important for successful functioning. The Self-Regulatory Strength Model (SRSM) proposes that all acts of self-regulation draw on a common and limited pool of self-regulatory energy, leading to self-regulatory failure if it is depleted. In contrast, Self-Determination Theory (SDT) proposes that people can regulate themselves for different reasons, with different consequences for both energy and success. More specifically, intrinsic motivation and autonomous extrinsic motivations for regulation are hypothesized to result in maintenance or increase of energy and successful self-regulation. Only controlled regulation is postulated to be associated with feeling drained. This thesis tests these competing views in a series of five studies (total N=1316). Using survey and laboratory methodologies, results revealed that self-regulation is not depleting to all participants. Participants regulate themselves for different reasons, and these motivational orientations are associated with different consequences for vitality and self-regulation. Intrinsic motivation was found to be associated with an increase in energy, while autonomous extrinsic motivation was associated with maintaining one's energy. Only controlled motivation was associated with a decrease in energy. In addition, intrinsic and autonomous motivations were directly associated with successful self-regulation on all measures: self-relevant activities; schoolwork and exercise; frustrating laboratory tasks and a global measure of success. These findings suggest that the processes proposed by the SRSM may be more closely associated with a controlled form of motivation for an activity. In other words, it is not the self-regulation of an activity itself that depletes energy; rather it is the way an activity is regulated that makes it draining. This suggests that fostering intrinsic motivation and internalization of extrinsic motivation should lead to an increase in vitality and success at self-regulation. In contrast, pressuring people to perform behaviors depletes their energy and indirectly leads to failure at self-regulation.
Keywords: Psychology, Behavioral.; Psychology, General.